PENGARUH GAYA KEPEMIMPINAN PATERNALISTIS DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING DI PT. PARKLAND WORLD INDONESIA 1-SERANG - Billy Tejaarief; Nita Afrillia (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
The purpose of this study was to see the direct and indirect influence between the variables of paternalistic leadership style (X1), work environment (X2), organizational commitment ( Z ) on employee performance ( Y ). The research method used in this study is a survey method with a correlational quantitative approach, the data analysis technique used in this study uses parametric statistical data analysis techniques. The analytical tools used for hypothesis testing in this study include multiple regression analysis using SPSS version 26 which is then followed by path analysis. The number of samples in this study was 103 employees of PT. Parkland World Indonesia 1-Serang. The results of the study state that the Paternalistic Leadership Style (X1) has a direct and significant influence on organizational commitment ( Z ), the Work Environment (X2) has a direct and significant influence on organizational  commitment ( Z ), Paternalistic Leadership Style (X1) and Work Environment (X2) have a direct and direct influence on organizational commitment ( Z ), Paternalistic Leadership Style Variable (X1) has a direct and significant influence on employee performance ( Y ), Work Environment (X2) has a direct and significant influence on organizational commitment ( Z ), organizational commitment ( Z ) has a direct and significant influence on Employee Performance ( Y ), Paternalistic Leadership Style (X1 ), Work Environment (X2), and Organizational Commitment ( Z ) have a joint and direct influence on Employee Performance ( Y ), Paternalistic Leadership Style Variable (X1) has Indirect influence on Employee Performance ( Y ) with Organizational Commitment ( Z ) as Intervening Variable and Work Environment Variable (X2) has an indirect effect on Employee Performance ( Y ) with Organizational Commitment ( Z ) as Intervening Variable